THE POLITICS OF MATARAM KINGDOM DURING THE REIGN OF SULTAN AGUNG - Ibnu Burdah (JOURNAL OF INDONESIAN ISLAM, 2017)
The period of Sultan Agung (1613-1645) is seen as the golden era of Mataram-Islam thanks to its various achievements in military, political, socio-cultural, and religious aspects while, in fact, the Kingdom was facing grave challenges both internally and externally including the fragmentation of Java into many conflicting small kingdoms, the dominance of VOC in Batavia, the threat of social fragmentation due to the divided stances between those keeping a Hindu culture and those adopting an Islamic worldview, as well as the penchant for rebellion among the noblemen in the conquered areas. This article asks the question of what kinds of politics and praxis the Kingdom of Mataram-Islam carried out in the midst of such grave challenges that it achieved a golden age. The result shows that the Kingdom founded its political vision of the unification of Java by strengthening the Javanese-Islamic identity in the midst of the Javanese Muslims who were clinging to the Javanese-Hindu tradition. The praxis it carried out included waging wars against the neighboring powers, sending two major expeditions against the VOC in Batavia, marrying the royal family members off to the rulers of the conquered regions, and synthesizing Islamic worldview and Javanese culture.